Entre os caminhos da docência: elementos constitutivos da identidade profissional de professoras de bebês no município de Ponta Grossa – PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
This study constitutes a doctoral research of the Postgraduate Program in Education of the State University of Ponta Grossa, in the Teaching and Learning line and has as its research object the professional identity of Early Childhood Education teachers who work with babies. The changes in the scope of Early Childhood Education invite us to reflect on a new structure of proposals aimed at childhood and raise questions about the professional identity of teachers of babies. Considering that identity is complex and has its singularities, we recognize that teachers are in a continuous process of constituting their identity. With the understanding that identity is the result of a social construction, this research focuses on the following problematizing question: What are the constitutive elements of the professional identity of babies teachers? Therefore, we chose as the general objective of this study to analyze the constitutive elements of the professional identity of babies teachers, taking into account the knowledge and teaching practices experienced in the context of daycare. The theoretical framework adopted to support the object of this research was based on Bourdieu's epistemological perspective (1983, 1994, 2004), which used the concepts of field and habitus, and on studies on the concept of identity constructed by Dubar (2005; 2009). This research was motivated by the thesis that there are specificities in teaching infants, and that the experiences, beliefs, personal and professional experiences of each teacher, the relationships established in the daycare routine and the recognition of the profession reflect on the constitution of their professional identity as teachers. Regarding the characterization of the investigative path, the research is of a qualitative nature and to achieve the proposed objectives, data were collected through online questionnaires and semi-structured interviews. The research agents are 46 babies teachers from the municipal and private schools in the city of Ponta Grossa, PR. Among the teaching paths, it is clear that the professional identity of teachers who work with babies in the city of Ponta Grossa - PR, is formed by several interconnected elements that reflect personal, academic, pedagogical, social and affective aspects. Each of these elements contributes to the constitution of professional identity, guided by teaching knowledge and the specificities of working with babies. The main elements that make up this identity include: the personal and family background of teachers, considering their first steps in choosing the profession; teaching knowledge and the specificities of teaching practice with babies; the marks of initial and continuing education in the professional career of teachers; and the identity and recognition of their profession in the social environment in which they are inserted. The relationship between habitus and teaching identity is considered to be close, as habitus contributes to the formation of this identity, offering a basis of behaviors and values with which teachers identity.
Keywords: identidade profissional docente; formação de professores; educação infantil; creche; professoras de bebês; professional teaching identity; teacher training; early childhood education; daycare; teachers of babies; Educação